2021
DOI: 10.1002/14651858.cd013836.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic regimens for late-onset neonatal sepsis

Abstract: Analysis 4.1. Comparison 4: Meropenem versus standard care (ampicillin plus gentamicin or cefotaxime plus gentamicin), Outcome

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 200 publications
0
26
0
1
Order By: Relevance
“…30 However, data in neonates and young infants in many LMIC settings are scarce. 15,31 A limited number of largely retrospective observational studies have shown an increase in mortality particularly in association with resistant Gram negative infections 3235 , such as those due to organisms producing extended spectrum beta-lactamases (ESBL) 3 -39 and carbapenem resistant organisms (CRO), 4043 and some suggest an increase in mortality in the absence of appropriate antimicrobial therapy. 32,4447 A recent large multicentre neonatal sepsis study (BARNARDS) demonstrated high resistance to ampicillin + gentamicin (97% and 70%, respectively) among Gram-negative infections; however, analysis of the influence of antibiotic treatment on outcomes was confounded by country effects, and limited clinical data prevented adjusting for other important confounders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30 However, data in neonates and young infants in many LMIC settings are scarce. 15,31 A limited number of largely retrospective observational studies have shown an increase in mortality particularly in association with resistant Gram negative infections 3235 , such as those due to organisms producing extended spectrum beta-lactamases (ESBL) 3 -39 and carbapenem resistant organisms (CRO), 4043 and some suggest an increase in mortality in the absence of appropriate antimicrobial therapy. 32,4447 A recent large multicentre neonatal sepsis study (BARNARDS) demonstrated high resistance to ampicillin + gentamicin (97% and 70%, respectively) among Gram-negative infections; however, analysis of the influence of antibiotic treatment on outcomes was confounded by country effects, and limited clinical data prevented adjusting for other important confounders.…”
Section: Discussionmentioning
confidence: 99%
“…After initial therapy, 728/2880 (25.3%) who started on Group 1-4 regimens were escalated to a higher group regimen, the majority switching within the first days of treatment (supplement figures [15][16][17]. 258/814 (31.7%) infants escalated from Group 1 (ampicillin/gentamicin) regimens, the majority of which switched to Group 2 (cefotaxime/ceftriaxone-based) regimens (61.6%, n=159) (figure 1c).…”
Section: Antibiotic Switchingmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggest further RCTs of different antibiotic regimens in late-onset neonatal sepsis are required. 25 Flannery et al the emergence of multidrug-resistant microorganisms requiring Surveillance and prevention is a paediatric research priority. Extended-spectrum β–lactamase (ESBL)-producing Enterobacterales and carbapenem-resistant Enterobacterales (CRE) are increasing and their impact on morbidity and novel antibiotic therapies are required.…”
Section: Treatments and Future Plans In Paediatric And Neonatal Sepsismentioning
confidence: 99%
“…( 118 - 120 ) A 2021 Cochrane systematic review assessed the effects of different LOI regimens, and similar to the previously discuss EOI Cochrane review, found that all analyzed trials were at high risk for bias and provided low-quality evidence. ( 121 ) Prescribers must therefore balance the risk of suboptimal empiric coverage with excessive coverage; the issue is complicated by a lack of clarity as to whether suboptimal early coverage impacts relevant clinical outcomes. The World Health Organization recommends ampicillin and gentamicin as first line therapy for neonatal sepsis in LMIC, and 3 rd generation cephalosporins as second line.…”
Section: Empiric Therapymentioning
confidence: 99%